Radiolucent metallic foreign body: a case report - Mir, Zahed Hussain; Kamal Osman Hassan; Issa, Mohammad Ridha; Jaiganesh, T. T. (International Journal of Contemporary Pediatrics, 2023)
A 13-year-old boy who accidentally ingested an aluminum beverage can pull tab. Neck and chest radiographs did not reveal any ingested foreign body. This case report illustrates poor negative predictive value of conventional radiographs for a suspected aluminum foreign body and demonstrates superiority of CT for this purpose. In such presentations, it is imperative to have a low threshold for performing further diagnostic evaluation with CT due to the relatively high radiolucency of aluminum.